2018
DOI: 10.1016/j.ebiom.2018.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin is a senotherapeutic that extends health and lifespan

Abstract: BackgroundSenescence is a tumor suppressor mechanism activated in stressed cells to prevent replication of damaged DNA. Senescent cells have been demonstrated to play a causal role in driving aging and age-related diseases using genetic and pharmacologic approaches. We previously demonstrated that the combination of dasatinib and the flavonoid quercetin is a potent senolytic improving numerous age-related conditions including frailty, osteoporosis and cardiovascular disease. The goal of this study was to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
541
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 703 publications
(592 citation statements)
references
References 85 publications
8
541
1
3
Order By: Relevance
“…After reaching adulthood, the senescence and SASP markers were significantly increased in multiple tissues and by multiple measures, and continued to rise as the animals aged (Figures and ). This correlates with the onset and progression of age‐related pathologies in multiple tissues of the Ercc1 − /∆ model (Dolle et al, ; Gregg et al, ; Gurkar & Niedernhofer, ; Harkema et al, ; Yousefzadeh et al, ; Yousefzadeh, Zhu, et al, ), providing further evidence that senescent cells play a causal role in numerous age‐related pathologies (Baker et al, ).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…After reaching adulthood, the senescence and SASP markers were significantly increased in multiple tissues and by multiple measures, and continued to rise as the animals aged (Figures and ). This correlates with the onset and progression of age‐related pathologies in multiple tissues of the Ercc1 − /∆ model (Dolle et al, ; Gregg et al, ; Gurkar & Niedernhofer, ; Harkema et al, ; Yousefzadeh et al, ; Yousefzadeh, Zhu, et al, ), providing further evidence that senescent cells play a causal role in numerous age‐related pathologies (Baker et al, ).…”
Section: Discussionmentioning
confidence: 78%
“…Likewise, senescence marker expression was elevated in the skin of both aged wild‐type and progeroid mice. Peripheral T cells and skin, which are readily accessible organs, or the aorta, with its large dynamic range of senescence marker expression, may prove useful for measuring the response to senolytic interventions in mice (Yousefzadeh, Zhu, et al, ). We did not detect increased expression of p16 Ink4a and p21 Cip1 in skeletal muscle or the heart of aged WT or young adult Ercc1 − /∆ mice (Figure b–c).…”
Section: Discussionmentioning
confidence: 99%
“…The use of p16‐3MR mice to perform longitudinal tracking and elimination of p16‐high cells provided evidence for the beneficial role of senescence in wound healing (14) and demonstrated that clearance of senescent cells could ameliorate age‐related diseases such as atherosclerosis (40) and OA (9). The knock‐in p16 LUC allele has been used to assess the senescence burden after senolytic treatment (41), and the p16 tdTom allele extends the analysis capabilities through the isolation of p16‐high and p16‐low cells with flow cytometry cell sorting.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a panel of flavonoid polyphenols distinct from quercetin has been screened for senolytic activity. Fisetin reduced senescence markers in multiple tissues in progeroid and naturally aged mice (Yousefzadeh et al , ), and administration of fisetin in normally aged mice restored tissue homeostasis, reduced age‐related dysfunction and extended lifespan. Future therapeutic outcomes will be required for initial proof of principle of combination therapies.…”
Section: Introductionmentioning
confidence: 99%